2022
DOI: 10.3390/genes13101873
|View full text |Cite
|
Sign up to set email alerts
|

VDR Polymorphic Variants Are Related to Improvements in CRP and Disease Activity in Patients with Axial Spondyloarthritis That Undergo Anti-TNF Treatment

Abstract: Vitamin D deficiency is related with susceptibility or progression of various autoimmune diseases. The aim of the study was to assess potential relations between single nucleotide polymorphisms (SNPs) in the vitamin D receptor-coding gene (VDR): rs1544410 (BsmI), rs2228570 (FokI), rs731236 (TaqI), rs7975232 (ApaI), and disease activity in patients with axial spondyloarthritis (axSpA) undergoing anti-TNF therapy. The VDR rs731236 CT genotype was statistically more common among female patients (p = 0.027). An im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…It is now known that polymorphisms of the VDR gene can lead to functional changes modulating the regulatory effects of vitamin D, as well as in the immune response. Indeed, associations between clinical response or remission during anti-TNFα therapy and VDR polymorphisms has been reported [15,16], but to our knowledge, this is the first study that has investigated the possible involvement of rs11568820 SNP in TNF-i treatment response.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is now known that polymorphisms of the VDR gene can lead to functional changes modulating the regulatory effects of vitamin D, as well as in the immune response. Indeed, associations between clinical response or remission during anti-TNFα therapy and VDR polymorphisms has been reported [15,16], but to our knowledge, this is the first study that has investigated the possible involvement of rs11568820 SNP in TNF-i treatment response.…”
Section: Discussionmentioning
confidence: 95%
“…Cusato et al described an association between VDR rs1544410 SNP and clinical remission at three months of TNF-i therapy in patients with inflammatory bowel disease (IBD) [15]. A study in patients with axial spondyloarthritis showed different improvements in C-reactive protein (CRP) and disease activity scores after 3 and 6 months of TNF-i therapy, depending on the genotype of the VDR polymorphisms rs2228570, rs731236 and rs7975232 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it reported associations of this genotype with clinical phenotypes of SLE and pSS. Lastly, the GG genotype of rs731236 was associated with a lower RA susceptibility Axial Spondyloarthritis Bugaj B, 2022[ 65 ] Poland Case-Control 106/122 42,7 (±12.9)/NA PCR-RFLP No VDR Fok I (rs2228570), Bsm I (rs1544410), Apa I (rs7975232) and Taq I (rs731236) No associations were identified between any of the studied polymorphisms and disease susceptibility. The study found higher prevalence for the rs731236 CT genotype among female patients compared to males.…”
Section: Resultsmentioning
confidence: 99%